Unveiling the Facets of Virtual Research Culture - Danganan, Catherine G. (Future Science / FSH-PH Publications, 2022)
With the ongoing trends due to the sudden outbreak of COVID-19, the researcher aims to unfold the perspectives and experiences of teachers, students and administrators in the prevailing research culture of higher educational institutions in an online learning setting during the pandemic. Higher educational institutions aim to strengthen the culture of sharing knowledge, resources, and best practices especially in the area of research. A narrative inquiry was conducted among twelve (12) key informants. Thematic analysis and data triangulation was used in analyzing the data. The findings were three overarching themes which are features of virtual research culture, depiction of virtual research experiences and manifestations in sustaining research culture during the pandemic. The findings further recommended to have a strong and intact leadership which is clearly focused on sustaining the research goals and targets of an institution. This also ensures that the members of an institution embrace a rich and formidable research culture. Likewise having a compelling and research-oriented leaders may encourage the whole university to engage on research activities. There might be virtual limitations encountered but a positive and goal-oriented institution will survive even in the midst of the pandemic.